2015
DOI: 10.1186/s12955-015-0377-3
|View full text |Cite
|
Sign up to set email alerts
|

Population preference values for health states in relapsed or refractory B-precursor acute lymphoblastic leukemia in the United Kingdom

Abstract: BackgroundTo date, reliable and comprehensive health-related quality of life data for patients with relapsed or refractory B-precursor acute lymphoblastic leukemia (ALL) have not been collected in clinical trials of the disease, and no utility studies have been published. The purpose of this study was to define and validate health states experienced by adults with relapsed/refractory B-precursor ALL, and to assign utility values to these health states using time-trade off methodology.MethodsThis study was cond… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
6
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 17 publications
2
6
0
Order By: Relevance
“…Health utility characterizes quality of life, which ranges from 0 (death) to 1 (perfect health). We obtained health utility scores for separate health states from the literature (37)(38)(39)(40)(41)(42). For patients experiencing toxicity, we subtracted health utility from their baseline scores.…”
Section: Outcomes Measuresmentioning
confidence: 99%
“…Health utility characterizes quality of life, which ranges from 0 (death) to 1 (perfect health). We obtained health utility scores for separate health states from the literature (37)(38)(39)(40)(41)(42). For patients experiencing toxicity, we subtracted health utility from their baseline scores.…”
Section: Outcomes Measuresmentioning
confidence: 99%
“…Although preference values aligned with clinical perception for AML as a disease, they generally represented other acute leukemias as milder disease. Health state utility values derived from a preference elicitation study conducted in the UK for patients with relapsed/refractory acute lymphoblastic leukemia (R/R ALL) demonstrated higher score values compared with AML preference values obtained in this study [ 26 ]. Although progressive disease (0.3) was not an HS defined in this study, it is akin to the relapse HS (0.1) used herein and was valued higher in patients with ALL.…”
Section: Discussionmentioning
confidence: 95%
“…These searches suggested that most studies reported data from patients only after they have recovered [12]. Aristides et al report values for adults with acute lymphoblastic anemia; with 0.50 for partial recovery after BMT and 0.30 for progressive disease [13]. Similarly, in acute myeloid leukemia Castejón et al (2018) report utility estimates of 0.28 for BMT; and 0.36 for chemotherapy during a month long hospital stay [14].…”
Section: Discussionmentioning
confidence: 99%